Ageing trajectories in football: Insights from the chinese super league on positional performance dynamics - Cao, J.; Zhou, C.; Liu, F.; Zhang, W.; Gómez, M.; Ortega-Toro, E. (International Journal of Performance Analysis in Sport, 2025)
This study examined the impact of age on the physical and technical performance of professional football players across different positions. Using 28,209 player-match observations from 2012 to 2021, covering 18 performance indicators, players were grouped into five positions: central defenders, fullbacks, central midfielders, wide midfielders and forwards. Generalized Additive Models (GAMs) were applied to identify nonlinear age-related patterns. The findings revealed distinct developmental trajectories and fluctuations at key age points, notably at 22, 25 and 30*years. Physical performance indicators for central defenders and fullbacks generally declined with age, although fullbacks maintained a stable level of high-speed running between 25 and 30*years. In terms of technical performance, central defenders showed gradual improvements in passing accuracy and ball retention with age, while fullbacks experienced stabilisation after 25. Central midfielders reached their physical peak between 22 and 32*years, and wide midfielders showed slight recovery in high-speed running after 30. As for forwards, their tactical value increased primarily through improved goal-scoring efficiency with age, although their role in organising play and ball control remained limited.